2001
DOI: 10.1038/modpathol.3880346
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Androgen Receptors in the Clinical Course of Nevus Sebaceus of Jadassohn

Abstract: Nevus sebaceus of Jadassohn (NSJ) is a benign, congenital hamartoma that often presents at birth, appears to regress in childhood, and grows during puberty, suggesting possible hormonal control. We studied 18 cases of NSJ from children and adults for immunohistochemical evidence of androgen receptor expression. The lesions were evaluated for location and pattern of immunostaining, and these findings were compared between age groups, sexes, and to androgen receptor expression in normal skin. Androgen receptor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 12 publications
4
29
0
Order By: Relevance
“…It has been shown that activated androgen receptors (ARs) can bind to the HRE and block the transcription of maspin in prostate cancer cell lines [35]. ARs are ubiquitously distributed in the human body, and it would be tempting to speculate that ARs play a role in the regulation of maspin expression in cutaneous structures [2,3,8,29]. In the skin ARs are consistently observed in seboblasts and in a variable proportion of sebocytes [3,8,29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that activated androgen receptors (ARs) can bind to the HRE and block the transcription of maspin in prostate cancer cell lines [35]. ARs are ubiquitously distributed in the human body, and it would be tempting to speculate that ARs play a role in the regulation of maspin expression in cutaneous structures [2,3,8,29]. In the skin ARs are consistently observed in seboblasts and in a variable proportion of sebocytes [3,8,29].…”
Section: Discussionmentioning
confidence: 99%
“…ARs are ubiquitously distributed in the human body, and it would be tempting to speculate that ARs play a role in the regulation of maspin expression in cutaneous structures [2,3,8,29]. In the skin ARs are consistently observed in seboblasts and in a variable proportion of sebocytes [3,8,29]. In other cutaneous structures, such as dermal papilla of hair follicles, hair follicle epithelial cells, eccrine and apocrine sweat glands, and keratinocytes, ARs show highly variable expression [3,8,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During puberty, lesions increase in size and develop a more verrucous and greasy texture. This is thought to be related to increased circulating androgens stimulating nevus components, including sebaceous glands, keratinocytes, apocrine, and eccrine glands, which express upregulated androgen receptors in NS [14]. Secondary eczematization, similar to Meyerson's phenomenon in melanocytic nevi, has been recently reported in association with NS [15].…”
Section: Nevus Sebaceousmentioning
confidence: 97%